p42_013 - + 1 == 1 (91 / 9) 1 + 1 = 0 . 91 , where we use E...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
13. Let E 1 =63meV+ E F and E 2 = 63 meV + E F . Then according to Eq. 42-6, P 1 = 1 e ( E 1 E F ) /kT +1 = 1 e x +1 where x =( E 1 E F ) /kT .W eso lv efo r e x : e x = 1 P 1 1= 1 0 . 090 1= 91 9 . Thus, P 2 = 1 e ( E 2 E F ) /kT +1 = 1 e ( E 1 E F ) /kT +1 =
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: + 1 == 1 (91 / 9) 1 + 1 = 0 . 91 , where we use E 2 E F = 63 meV = E F E 1 = ( E 1 E F )....
View Full Document

Ask a homework question - tutors are online